CHARACTERIZATION OF SACCHARIDE SUGAR IN CORN SEED (Zea Mays Saccharata) BY USING GAS CHROMATOGRAPHY MASS SPECTROMETRY METHOD - Asfar, Andi Muhamad Iqbal Akbar (Jurnal Bahan Alam Terbarukan, 2018)
This study characterizes the saccharide sugar contained in whole sweet corn seeds by extracting using Ultrasound Assisted Solvent Extraction for 60 minutes with 24 kHz frequency using ethanol solvent with concentrations of 70%, 75%, 80%, and 85%. The concentrated extract was then characterized by using Gas Chromatography Mass Spectrometry (GCMS) method. Sample test conducted were tested to odor, color and shelf life of extract and determination of water content, ash content, and characterization of saccharide sugar from GCMS test. The odor and color test results show that the extract had a distinctive smell of sweet corn, yellow, and had the ability to store good extract in the condition of the room. The water content of each sample ranged from 3% - 9% with the lowest water content was in 85% concentration sample which was 3.62%, while the ash content ranged from 1.5% with the highest ash content which was in 85% concentration sample which was 1.59%. The results of characterization were identified by 3 compounds having the highest percentage of 2-Furaldehyde, Hexamethyl Cyclotriloxane, and 1,2,4-Trimethyl Benzene with the percentage of 26,94%, 9,95% and 13,82% respectively. 2-Furaldehyde includes heterocyclic aldehyde group sugars, whereas Hexamethyl Cyclotriloxane and 1,2,4-Trimethyl Benzene belong to the class of organosilicon and aromatic hydrocarbons. 2-Furaldehyde or Furfural serves as a tongue nerve stimulator and has great potential to be developed as an important non-petroleum-based chemical raw material. The GCMS results provide information that the obtained 2-Furaldehyde has a molecular formula C5H4O2 or C4H3OCHO which is a monosaccharide group which is aldose with the number of C atoms classified as pentose. The retention time was 3.062 minutes with a mass peak of 300 m/z with molecular weight was 96 g/mol.